The Historical Ecology of Abalone (Haliotis Corrugata and Fulgens) in the Mexican Pacific - Revollo Fernández, Daniel A.; Sáenz-Arroyo, Andrea (México y la Cuenca del Pacífico, 2015)
Abalone shells and meat played and play an important role in the rich economic, social y cultural history of Baja California. Chinese and Japanese fishermen and later the consolidation of Mexican cooperatives have all fished in this region. Information obtained through surveys and oral history from three generations of abalone divers on Baja California has revealed that over time catches have decreased and the organisms fished have reduced their size. The decrease in catch size and weight described by the divers generate an approximate 70% reduction in abalone’s reproductive capacity. Resumen: Conchas y carne de abulón desempeñaron y desempeñan un rol importante en la rica historia económica, social y cultural de Baja California, México. En la región pasaron desde pescadores chinos, japoneses hasta la consolidación de cooperativas mexicanas. Información obtenida a través de entrevistas, reportes históricos e historia oral de tres generaciones de buzos de abulón revela la reducción tanto en capturas como en tamaño del organismo. Esta reducción genera una disminución aproximada del 70% en la capacidad reproductiva de este molusco.